Does internet use affect levels of depression among older adults in China? A propensity score matching approach - Wang, Yean; Zhang, Huan; Feng, Tong; Wang, Hongyang (BMC public health, 2019)
Emerging research on the use of new technology suggests that internet use is generally associated with high levels of efficiency among older adults in the following areas: quality of life, mood, positive psychological well-being, and the individual and societal costs of caring for them. However, there is little empirical evidence specifically concerning the causal effects of older adults' internet use on their depression level. There is a need for more replication studies to help confirm that the emerging evidence on the impact of internet use is accurate and applicable to different populations and in different situations. Using national data from the China Family Panel Study in 2016, this study helps to fill the above mentioned research gap. This study followed a two-step analytical strategy to empirically examine the association between internet use and reported depression in older adults. In the first step, we estimated a binary logistic regression model with internet use as the dependent variable and 8 demographic and socioeconomic factors as the confounding variables. In the second step, we performed a propensity score analysis to control for potential bias using the confounding variables confirmed in the first step. The results show that older adults who reported internet use have lower depression levels than did those who did not use the internet, with adjustments made for gender, age, urban or rural residence, pension status, educational background, physical health, life satisfaction, and intelligence level. These findings suggest that it is critical to advocate for technology-based policies and programs that promote older adults' internet use to improve their social well-being, which can also serve as a policy strategy to help alleviate older adults' depression.